Autofluorescence-Guided Surgery in the Management of Osteonecrosis of the Jaw: Correlation Between Bone Autofluorescence and Histopathological Findings in 56 Samples - Ilaria Giovannacci; Aurora Andrea Venuti; Luigi Corcione; Samir Nammour; Paolo Vescovi (Life)
(1) Background: Osteonecrosis of the jaw (ONJ) remains a challenging condition without a universally accepted treatment protocol. Surgical therapy, particularly Er:YAG laser-assisted surgery, has shown more predictable long-term results compared with non-surgical options. However, the identification of resection margins in ONJ surgery is complex and currently relies on the surgeon’s intraoperative assessment, without standardization. Bone autofluorescence (AF) has been proposed as an intraoperative diagnostic tool for visualizing necrotic bone; under VELscope (LED Medical Diagnostics Inc., Barnaby, BC, Canada) illumination, healthy bone exhibits hyperfluorescence, while pathological bone appears dark brown/black (loss of autofluorescence, LAF). (2) Methods: 22 patients with ONJ requiring surgical therapy were included. After bone exposure, VELscope system was used to induce and visualize bone AF. Areas exhibiting absent or pale AF were identified as necrotic and removed; additional samples were collected from adjacent hyperfluorescent regions. (3) Results: Histopathologic evaluation of 56 specimens were conducted; 35 hypofluorescent samples were found to be necrotic bone tissue; in the 21 hyperfluorescent samples, 86% demonstrated normal, vital bone. The correlation between fluorescence and bone vitality was highly significant (p < 0.0000001). (4) Conclusions: Our data show that AF-guided surgical resection, combined with Er:YAG laser-assisted surgery, may improve clinical outcomes.